Peran karakteristik wirausahawan dan kemampuan usaha terhadap keberhasilan usaha di masa pandemi - Susi Widjajani; Ridwan Baraba; Rifi Handayani (Jurnal Manajemen Maranatha, 2021)
One of the sectors affected by the coronavirus (Covid-19) pandemic is small business. Its existence, which is essential in supporting the regional economy, is getting worse and requires more efforts to be able to survive during this pandemic. From the demand side, mainly consumption and purchasing power, its performance has decreased, thus disrupting the production process and business success. The role of entrepreneurs is needed to be able to achieve business success. This study aims to examine the role of business ability as a mediating variable on the effect of entrepreneur characteristics on business success. The population of this study is small snack entrepreneurs in Purworejo Regency. Sampling using purposive sampling technique with a total of 100 respondents. This study used a survey method to collect data with the help of a questionnaire. Furthermore, the data is processed using the Hierarchical Regression Analysis method. The results of the study show that the characteristics of entrepreneurs and business abilities partially influence business success. Characteristics of entrepreneurs affect business ability, and business abilities can mediate the influence of entrepreneurial characteristics on business success. The real contribution of the results of this study is expected for snack food entrepreneurs in Purworejo Regency during this pandemic to be able to achieve business success, especially about the characteristics and abilities that small entrepreneurs must possess to survive in a pandemic situation like this.